ANALISIS PRAKTIK AKUNTANSI DALAM WURUMANA (KEMATIAN) DI ERA MODERNISASI PADA ULAYAT LOKOBOKO (Studi Kasus di Kampung Sokomaki, Kelurahan Lokoboko, Kecamatan Ndona, Kabupaten Ende) - Apriana Marselina; Nuraini Ismail; Yohana Mariani Sene Tei (Jurnal Mirai Management, 2023)
The research aims to examine accounting methods in Wurumana (death) during the modernization era in Lokoboko Ulayat (Case Study in Sokomaki Village, Lokoboko Village, Ndona District). Wurumana is the same traditional event, namely a traditional activity carried out or planned by a family and involving all other family members, both close and distant families, in specified event conditions.This study approach employs qualitative analysis of the Wurumana process's results through interviews, observations, and literature studies. This study is being conducted in Sokomaki Village, Ndona District, Ende Regency. Primary data gathered from interviews and secondary data obtained from books related to the research title were used in this study. This study generates data that can be utilized as information material and consideration for belis in accounting, such as: (1) The accounting technique of implementing debt in Wurumana/wai-rhaki (Death) is consistent with Financial Accounting Standards since there are two categories of debt used, namely long-term debt and current debt. (2) The practice of cost management accounting in Wurumana/wai-rhaki (Death) is consistent with Financial Accounting Standards since managing costs involves the sacrifice of economic resources in order to achieve assets or anything needed. Every receipt and expenditure recorded by the bereaved family demonstrates this. (3) The rise of a more modern era has an impact on the methods and stages of Wurumana/wai-rhaki implementation, particularly where innate material talents are concerned. Keywords: Wurumana, Debt, Costs, Accounting, Death